Indigenous Peoples and research: self-determination in research governance - Garba, Ibrahim; Sterling, Rogena; Plevel, Rebecca; Carson, William; Cordova-Marks, Felina M.; Cummins, Jewel; Curley, Caleigh; David-Chavez, Dominique; Fernandez, Adam; Hiraldo, Danielle; Hiratsuka, Vanessa; Hudson, Maui; et al. (Frontiers in Research Metrics and Analytics, 2023)
Indigenous Peoples are reimagining their relationship with research and researchers through greater self-determination and involvement in research governance. The emerging discourse around Indigenous Data Sovereignty has provoked discussions about decolonizing data practices and highlighted the importance of Indigenous Data Governance to support Indigenous decision-making and control of data. Given that much data are generated from research, Indigenous research governance and Indigenous Data Governance overlap. In this paper, we broaden the concept of Indigenous Data Sovereignty by using the CARE Principles for Indigenous Data Governance to discuss how research legislation and policy adopted by Indigenous Peoples in the US set expectations around recognizing sovereign relationships, acknowledging rights and interests in data, and enabling Indigenous Peoples' participation in research governance.